2021
DOI: 10.1159/000518040
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Improves the Symptoms of DHEA-Induced PCOS Rats by Regulating Gut Microbiotas and Metabolites

Abstract: <b><i>Objectives:</i></b> The aim of this study was to investigate the effects of berberine on polycystic ovary syndrome (PCOS) with insulin resistance (IR). <b><i>Design:</i></b> This study performed 16S rRNA sequencing and metabolomic analysis on dehydroepiandrosterone (DHEA)-induced PCOS rats treated with berberine, focusing on the improvement of PCOS-IR by modifying gut microbiota and metabolism. <b><i>Methods:</i></b> Forty-two female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Yu et al indicated that decreased endometrial receptivity and abnormal ovarian morphology existed in mice exposed by DHEA [25]. erefore, a rat model of PCOS induced by DHEA was established in the study, which showed typical PCOS-like symptoms like considerable increases in body weight and ovarian index, disruption of the estrous cycle, abnormal sex hormone levels, and abnormal ovarian morphology, in line with the previous study [26]. According to previous studies, acupuncture can relieve PCOS-like symptoms by balancing the levels of sex hormones and autophagy in ovarian tissues via regulating PI3K/ AKT pathway [27].…”
Section: Discussionsupporting
confidence: 81%
“…Yu et al indicated that decreased endometrial receptivity and abnormal ovarian morphology existed in mice exposed by DHEA [25]. erefore, a rat model of PCOS induced by DHEA was established in the study, which showed typical PCOS-like symptoms like considerable increases in body weight and ovarian index, disruption of the estrous cycle, abnormal sex hormone levels, and abnormal ovarian morphology, in line with the previous study [26]. According to previous studies, acupuncture can relieve PCOS-like symptoms by balancing the levels of sex hormones and autophagy in ovarian tissues via regulating PI3K/ AKT pathway [27].…”
Section: Discussionsupporting
confidence: 81%
“…In the study by Shen et al, clear changes in the composition of the intestinal microflora were found after the use of berberine. In terms of class assignment, Bacteroidetes and Firmicutes dominated, while at the genus level berberine significantly influenced the relative abundance of Romboutsia, Bacteroides [18]. This drug can effectively restore the normal composition of the bacterial flora, but further extensive research is needed to confirm this.…”
Section: Resultsmentioning
confidence: 98%
“…Owing to the ethical issues involved in direct intervention in patients with PCOS and the difficulty in operating on these patients, animal models of PCOS are widely used to study new treatments for the disease. Letrozole administration [59] and subcutaneous injection of DHEA [60] are the most commonly used modeling methods in current literature reports, so we chose these two models for a comparative study. The letrozole-induced mouse model has typical manifestations of PCOS, including oligoovulation, hyperandrogenism, polycystic ovarian degeneration, and abnormal metabolism.…”
Section: Discussionmentioning
confidence: 99%